An evolutionary approach to identify potentially protective B cell epitopes involved in naturally acquired immunity to malaria and the role of EBA-175 in protection amongst denizens of Bolifamba, Cameroon. (December 2016) - Nyasa, Raymond; Kimbi, Helen; Zofou, Denis; DeBarry, Jeremy; Kissinger, Jessica; Titanji, Vincent
Abstract Background The search for a vaccine against malaria caused byPlasmodium falciparum has lasted for more than 100 years, with considerable progress in the identification of a number of vaccine candidates. The post-genomic era offers new opportunities for an expedited search using rational vaccine design and prioritization of key B-cell epitopes involved in natural acquired immunity. Methods Malaria vaccine candidate genes that have reached clinical trial were searched on an evolutionary relationship tree, to determine their level of lineage-specificity. Ten other genes with similar protein features and level of lineage specificity to the vaccine candidates were randomly selected, and computationally evaluated for the presence of B-cell epitopes. The protein fragment with maximum probability of putative epitopes were synthesized and used in an ELISA experiment to determine the presence of antibodies to these peptides, in the serum of malaria patients and healthy malaria uninfected inhabitants from a malaria endemic region (Bolifamba), alongside with a vaccine candidate EBA-175. Results Two peptide fragments of 25 and 30 amino acid length from PF3D7_1233400 and PF3D7_1437500 respectively, coded as PF4-123 and PF4-143 were shown to contain B-cell epitope(s). Total IgG antibodies to these peptides were not significantly different between sick and healthy participants, but cytophilic antibodies to these peptides were significantly higher in healthy participants (p < 0.03). Total IgG to the vaccine candidate EBA-175 was significantly higher in sick participants than in healthy participants, likewise cytophilic antibodies (p < 0.04). Antibodies to the peptides PF4-123 and PF4-143 correlated negatively (p = 0.025 and 0.008 and r = −0.291 and −0.345, respectively) to parasite load. Total IgG antibodies to EBA-175 showed a negative correlation to parasite load (r = −0.144), which was not significant (p = 0.276). Duration of stay in Bolifamba also negatively correlated with parasite load (p = 0.026, r = −0.419) and total IgG to PF4-143 was significantly associated with prolonged duration of stay in the locality of Bolifamba, Cameroon (p = 0.006, r = 0.361). Conclusions The present study has identified two genes PF3D7_1233400 and PF3D7_1437500 containing peptide fragment (PF4-123 and PF4-143) with B-cell epitopes that are correlated with naturally acquired immunity to malaria. A pipeline has been developed for rapid identification of other B-cell epitopes involved in naturally acquired immunity.